Habitat preference by the Anatolian leopard (Panthera pardus tulliana Valenciennes, 1856) in North-eastern Anatolia, Turkey - Sari, Alptug; Gündoğdu, Ebubekir; Baskaya, Sagdan; Arpacik, Ahmet (Royal Belgian Zoological Soc, 2020)
This study aims to document the existence and habitat preferences of the Anatolian leopard (Panthera pardus tulliana Valenciennes, 1856) in north-eastern Anatolia, Turkey. We sampled eleven study areas in 2013-2017, primarily based on our previous field experiences, reports from local people, and literature. Based on the findings from initial surveys, camera traps and leopard studies were mostly used in parts of the Giresun (Saricicek Mountain), Erzincan (Sansa Strait), and Bingol (Yedisu Valley) Provinces. We employed both direct observations and indirect observations. A total of 58 observations were recorded, ranging from 1176-3050 meters in altitude: six camera trap pictures, three thermal video camera images, three sightings by local people, 28 sets of tracks, 13 pieces of scat, two ground-scrapings, and three tree-scratches belonging to the Anatolian leopard. We defined eight habitat types and found that leopards preferred sparse forest areas, rocky habitats, and agriculture and pasture regions the most. Furthermore, 49 of 58 observations made in the sampling areas were detected in the southerly aspects of the study region. The Anatolian leopard habitat selection is mainly based on prey abundance, and we found that leopards prefer wild boar (Sus scrofa) the most, followed by wild goat (Capra aegagrus), chamois (Rupicapra rupicapra), and roe deer (Capreolus capreolus).
Keywords: Camera trap; habitat use; Anatolian leopard; Panthera pardus tuttiana; thermal camera; Anatolia